(3GdLQGFO GdSjGSjI (B:s (3ChGeQ GdEYJbGd h bGfhf GdWhGQF (B/s - (3YHO GdMejO, GdThGQHjs ((3GdCScfOQjI(B- (3eUQ (B:s (3efTCI GdeYGQa HGdCScfOQjI ,s, 1989)
(3JYO GdLQGFe GdSjGSjI ef GNWQ GdLQGFe GdJDOj Gdi GdGYJOG Yd Gef GdOhdI GdOGNdj dPG abO GgJe Gdabg HJYQjagG h JMOjO fWGbgG h eVehfgG (B.(3dPG abO QGjJ LeY gPg GdGQGA h JUfjagG h JHhjHgG aj eDda hGMO jLeY TJGJgG GdfHYKQI aj GHMGK eJaQbI h bO bSe GdHMK Gdi bSejf(B: (3GdbSe GdGhd Yf GdLQjeI GdSjGSjI h GdbSe GdKGfj Yf GfXeI GdGMcGe GdYQajI h bGfhf GdWhGQF h JTQjYGJ Gef GdOhdIs
Keywords: (3GdLQGFO GdSjGSjIs; (3GdLQjeI GdSjGSjIs